Implementation of Productive Learning Innovations in Tourism Vocational Schools - Suwandi, Andreas; Ridwanudin, Oce; Pratama, Raditya (Journal of Tourism Education, 2022)
The nation's productivity and competitiveness is one of the keys to the revitalization of vocational high schools currently being implemented in Indonesia. Revitalization of Vocational High Schools can be used as a solution to produce students who are modern, dignified, innovative and creative. This study aims to find out 1) Efforts that have been made by SMK in implementing learning innovations; 2) Implementation of quality-based productive innovative learning innovations at tourism vocational schools in the Greater Bandung area; 3) An innovative learning model that is used to improve the quality of graduates through productive learning at Tourism Vocational Schools. 4) The obstacles to the implementation of graduate quality-based innovative learning found in Tourism Vocational Schools in Bandung Raya. This research is descriptive research, taking place in Tourism Vocational Schools in Bandung Raya. The sample of teachers is productive teachers who are members of the Tourism Vocational High School MGMP in the Tourism Sector of Bandung Raya Regency, totaling 30 teachers. The sample of students is the students of SMK Binawisata Lembang who are taught by one of the MGMP teachers. The instruments used were questionnaires and FGD guidelines. Data were analyzed using quantitative and qualitative descriptive results. The results showed that: 1) Not all teachers mastered the 4K concept well; 2) Not all teachers are able to implement 4K in learning; 3) 4K learning based on graduate quality, shows that not all teachers apply quality awareness in both design, implementation and evaluation; 4) the obstacles that teachers feel when learning 4K-based innovation are: integrating 4K into learning, difficulty making syntax, developing learning methods; 5) the obstacles felt by students were that most students stated that it was not so difficult to complete 4K learning tasks. The implementation of graduate quality-based innovation learning with a 4K learning orientation still requires more in-depth study, both through FGDs, class observations and review of lesson plans.